Relationship between the Second to Fourth Finger Length Ratio and Calcaneus Quantitative Ultrasound - Yoko Takahata; Kumi Hirokawa (Scientific Reports, 2018)
Abstract This study aimed to characterize the relationship between the ratio of the length of the second and fourth fingers (2D:4D value) and the speed of sound of the calcaneus by quantitative ultrasound (QUS-SOS) in undergraduate female students. We recruited 138 young women with a mean age of 19.6 ± 1.4 years. The participants’ calcaneus QUS-SOS was measured using an ultrasound bone densitometer. We also measured the participants’ weight, height, and grip strength. A self-reported questionnaire was used to obtain information on participants’ secondary sexual characteristics, and exercise habits. The present study showed that the 2D:4D value of both hands was significantly correlated with the calcaneus QUS-SOS. The 2D:4D value of the left hand was also positively associated with the calcaneus QUS-SOS results in several respects. These findings suggest that the 2D:4D value may be useful for the screening of risk for a low bone quality in undergraduate female students.